From research, through policy and politics to practice: learning from experience. Issue 1 (4th March 2014) - Davies, Emma; Rowe, Elizabeth
Abstract : Purpose: – The aim of this paper is on what the authors learnt from negotiating the difficult terrain linking, or separating, research from policy advice and the political process. Design/methodology/approach: – This paper outlines two case studies from New Zealand to examine what confounds and what bridges gaps between research, policy, politics and practice. The case studies were predicated on the belief that interagency and cross-sectoral actions were necessary to align actions and achieve good outcomes in social policy. Findings: – Interagency processes are not the Holy Grail. More attention needs to be paid to the impact of the context in which researchers, public servants and politicians operate and of the research and policy-making processes within their organisations. Politics within and between organisations and politics on the national stage must also be understood if the gap between research, policy and practice is to be narrowed and successfully navigated. Originality/value: – These are original case studies. Researchers often bemoan the failure of their findings to influence policy and practice; policy makers complain that researchers are unaware of "real world" timeframes and policy concerns, and politicians grow impatient with advice that takes little heed of political imperatives. Therefore, these case studies will be of particular interest to students and practitioners of social policy and researchers who wish to see their findings influence policy.